ChemInform Abstract: Ionic Liquids for Energy, Materials, and Medicine. Issue 38 (10th September 2014) - Smiglak, M.; Pringle, J. M.; Lu, X.; Han, L.; Zhang, S.; Gao, H.; MacFarlane, D. R.; Rogers, R. D.
Abstract Review: [258 refs.